(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The infection caused by the coronavirus pandemic (COVID-19) continues to show its clinical picture. Despite the publication of a number of scientific articles, the course of coronary heart disease in the acute phase of COVID-19, especially SARS-CoV-2, has been little studied. Separately obtained results of the disease require a thorough study of the effect of COVID 19 on the cardiovascular system.